2015
DOI: 10.7860/jcdr/2015/11296.5877
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiomatous Polyp of Palatine Tonsil in A Child Presenting with Dysphagia and Dysarthria

Abstract: A 14-year-old boy presented with one year history of mass in the oral cavity which was initially small and progressively increased in size. He complained of difficulty in speaking and swallowing since four months. There was no history of respiratory difficulty sore throat or bleeding. Patient was undergoing psychiatric treatment for behavioral problems and is on resperidone therapy. Otorhinological examination of oral cavity revealed a smooth pinkish white mobile nontender firm pedunculated mass arising from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Nevertheless, most authors agree that this condition has a higher incidence than reported because these masses can be overlooked in a routine examination and because of inconsistencies with their classification 1–6. Characteristically, a tonsillar lymphangioma may be reported in the literature under various terms like lymphangiomatous polyp, polypoid lymphangioma of the tonsil, lymphoid polyp, tonsillar angiofibroma, lymphangiectatic fibrolipomatous polyp, fibrolipoma, angiofibrolipoma, polypoid tumour containing fibroadipose tissue, hamartomatous tonsillar polyp and lymphangiectatic fibrous polyp 2 3 5 10. Notably, the last edition (5th) of the WHO classification of Head and Neck tumours uses the term ‘tonsillar hamartomatous polyp’ for a tonsillar lymphangiomatous polyp;20 thus, we comply with that terminology in our case report article.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, most authors agree that this condition has a higher incidence than reported because these masses can be overlooked in a routine examination and because of inconsistencies with their classification 1–6. Characteristically, a tonsillar lymphangioma may be reported in the literature under various terms like lymphangiomatous polyp, polypoid lymphangioma of the tonsil, lymphoid polyp, tonsillar angiofibroma, lymphangiectatic fibrolipomatous polyp, fibrolipoma, angiofibrolipoma, polypoid tumour containing fibroadipose tissue, hamartomatous tonsillar polyp and lymphangiectatic fibrous polyp 2 3 5 10. Notably, the last edition (5th) of the WHO classification of Head and Neck tumours uses the term ‘tonsillar hamartomatous polyp’ for a tonsillar lymphangiomatous polyp;20 thus, we comply with that terminology in our case report article.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangiomatous polyps are common in the low gastrointestinal tract, 3. However, tonsillar lymphangiomatous polyps are rare entities with sparse reports in the literature, 1–19. Nevertheless, most authors agree that this condition has a higher incidence than reported because these masses can be overlooked in a routine examination and because of inconsistencies with their classification 1–6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, pedunculated lymphoangiomatous polyp (PLP) of tonsils is extremely uncommon and there are only a few cases dedicated to this pathology [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…8 It has also recently been suggested that they may develop as a result of uncontrolled neoplastic proliferation of lymphatic vessels due to dysregulation of growth factors such as Prox-1 and vascular endothelial factor. 9 Lymphangiomatous polyps lead to swallowing difficulty, the sensation of foreign body in the throat, sore throat, and tonsillar mass. Respiratory difficulty and stridor may occur if the mass is very large.…”
Section: Case Reportmentioning
confidence: 99%